Evaluation of the Deployment Results of the Rosatom Production System and the Opportunity to Extrapolate Lean Technologies to the Social Sphere - Ukhalina, I. A.; Agapova, S. P.; Efimenko, N. A. (Глобальная ядерная безопасность, 2022)
The purpose of this study is to evaluate the results of the system deployment of the Rosatom Production System in five main areas and the possibility of transferring lean approaches and technologies used at Rosatom enterprises to the organization of the social sphere. In the process of studying the stated problem, such research methods as analysis and synthesis, the method of economic modeling are used. To assess the possibility of using lean technologies in social organizations, the method of extrapolating the resulting positive effect from the use of lean manufacturing at Rosatom enterprises to healthcare facilities is used. The article provides an assessment of the results of fulfilling the social order of nuclear cities through the implementation of social partnership programs for the Lean Polyclinic project. Based on the analysis of the results of using lean approaches in medical institutions in the pilot regions and to improve the quality of public services, it is proposed to introduce lean technologies in various non-manufacturing enterprises. The paper concludes that as a result of the partnership of effective Production systems and social enterprises, not only clinics, hospitals, but entire cities can be made convenient and comfortable